Diseño y construcción de un transportador de semielaborados para la fabricación de filtros de cigarrillos con capacidad de 5000 barras/min. - Pedraza Moromenacho, Víctor Hugo (2015)
This project is developed according to the needs of the company Tanasa, which is responsible for transporting semi - finished products processing machines at the cigarette filters. From a centralized ergonomic loading hopper avoiding direct and manual loadi ng as it is currently done. The first phase of the general and specific objectives, scope, justification, research methods and the theoretical basis of the parts of the conveyor is analyzed Then is performed the physical space sizing, design, calculations , selecting items using catalogs, place then choose the best construction option to transport semi flow required in each of the machines. We continue with the calculation of costs, local and imported materials, inputs and labor. Finally concluded as annex es. Maintenance plans and recommendations.